Aversion towards HIV antibody testing in a tertiary institution in Nigeria - Yusuf OB; Oladepo OO (Ibom Medical Journal, 2008)
CONTEXT: Students in tertiary institutions are at risk of contracting Human Immunodeficiency Virus (HIV) because they fall within the age group that is sexually active. In Nigeria little has been reported on knowledge and attitude towards HIV antibody testing in this population. METHODS: A cross sectional study of 400 students was conducted using a self administered questionnaire. Participants were questioned about their knowledge and attitude regarding HIV antibody testing. Descriptive analyses were performed. RESULTS: Knowledge of HIV testing was highest among male respondents (22.4%) compared with females (15.2%). (p=0.07).  However, knowledge about HIV testing centres was low with as high as 320 (80.0%) respondents not knowing any place. Attitude toward HIV testing was poor.  Almost all the participants, 391 (97.8%) claimed that they had never undergone HIV antibody testing. Lack of adequate information of HIV testing (13.9%) and fear of outcome of result were also responsible for aversion to HIV testing.